Sudden Sensorineural Hearing Loss in Hemodialysis Patients Could be a Marker of Pathogenic Progression in the Mortality and Atherosclerotic Events: A National Cohort Study. Issue 10 (December 2018) - Chou, Chu-Lin; Hsieh, Tsung-Cheng; Chen, Jin-Shuen; Fang, Te-Chao
Abstract : Objectives: There are higher incidence of sudden sensorineural hearing loss (SSHL) in hemodialysis (HD) patients than in the general population. Long-term outcomes of HD patients with new-onset SSHL have yet to be investigated although SSHL is considered as an independent risk of cardiovascular diseases in the general population. We examined the risks of mortality and atherosclerotic events in HD patients with new-onset SSHL in Taiwan. Study Design: Cohort study. Methods: Using the Taiwan National Health Institutes Research Database, 105, 243 HD patients were identified between 1997 and 2008. In total, 288 HD patients with a new diagnosis of idiopathic SSHL were enrolled and matched with 1, 728 HD patients without SSHL by using propensity score matching at a ratio of 1:6. Main Outcome Measures: A multivariate Cox regression and a competing risk regression were used to evaluate mortality and atherosclerotic events. Results: Results revealed a risk of mortality in HD patients with SSHL than in HD patients without SSHL (adjusted hazard ratios [aHRs] 2.22, 95% confidence interval [CI] 1.71–2.89). HD patients with SSHL had higher risks of hemorrhagic stroke (competing risk aHR 4.08, 95% CI 1.93–8.61), ischemic stroke (competing risk aHR 2.34, 95% CI 1.45–3.78), acute coronary syndrome, and peripheral arterial occlusive disease than did the HD patients without SSHL. Conclusion: This study is the first to signify that the risks of mortality and atherosclerotic complications in HD patients with new-onset SSHL are increased. Therefore, we should pay attention to risks of mortality and atherosclerotic events in HD patients with new-onset SSHL. Abstract : Supplemental Digital Content is available in the text